Enhancing Higher-order Thinking Skills in Chemistry Education: A Validated Canva-IBL-STEM Model for Stoichiometry Learning - Panggabean, Freddy Tua Musa; Sutiani, Ani; Purba, Jamalum; Dibyantini, Ratu Evina; Hasibuan, Muhammad Haris Effendi; Krisbiantoro, Philip Anggo (Jurnal Pendidikan IPA Indonesia, 2025)
Developing Higher Order Thinking Skills (HOTS) remains a major obstacle in the global drive for STEM education in the twenty-first century, especially in complex subjects like stoichiometry. Although Inquiry-Based Learning with STEM (IBL-STEM) fosters critical thinking and Canva is frequently used for educational design, no previous study has combined these strategies to solve the conceptual challenges of stoichiometry. This study aimed to create and verify a Canva-based stoichiometry teaching resource and examine its effectiveness in improving chemistry students' HOTS. We created interactive Canva modules with guided inquiry tasks, molecular visualization, and HOTS assessment using the ADDIE paradigm (Analysis, Design, Development, Implementation, Evaluation). The materials were tested with 62 students using pre-test/post-test comparisons and validated by three chemistry education specialists (mean feasibility scores: 4.71 for content and 4.74 for media). With post-test scores (76.94 ± 6.61) significantly surpassing pre-test findings (35.71 ± 6.36), the intervention significantly improved HOTS (mean gain: 41.23 ± 9.33, p < 0.001). The results of this study indicate that the Canva-IBL-STEM model is valid for implementation in stoichiometry learning and has been shown to improve students' HOTS abilities. The findings provide educators with a model for inquiry-driven, technology-enhanced learning that connects design tools with profound conceptual knowledge.